2016
DOI: 10.5817/bse2016-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-reference in research articles across Europe and Asia: a review of studies

Abstract: Numerous cross-linguistic and cross-disciplinary studies have looked at the manifestation of author stance in academic texts. One of the most recurrent areas of contrast has been the use of personal pronouns across linguistic and disciplinary cultures. This paper aims at reviewing previous research on self-reference in research articles taking an intercultural perspective. It focuses on 22 studies which report on results regarding this stance feature in 13 lingua-cultural contexts (Bulgarian, Chinese, Danish, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
9
4
Order By: Relevance
“…In contrast, Slovak single authors typically use authorial plural when writing both in non-native English (70%) and even more so in Slovak (90%), as observed previously in other Slavic languages (e.g. Chamonikolasová 2005, Čmejrková 2007, Dontcheva-Navratilova 2013, Mur Dueñas & Šinkūnienė 2016, Vassileva 1998, see Section 2). In the non-native English corpus, the singular perspective (30%) is used in nine papers out of 27 single-authored papers.…”
Section: (11)supporting
confidence: 64%
“…In contrast, Slovak single authors typically use authorial plural when writing both in non-native English (70%) and even more so in Slovak (90%), as observed previously in other Slavic languages (e.g. Chamonikolasová 2005, Čmejrková 2007, Dontcheva-Navratilova 2013, Mur Dueñas & Šinkūnienė 2016, Vassileva 1998, see Section 2). In the non-native English corpus, the singular perspective (30%) is used in nine papers out of 27 single-authored papers.…”
Section: (11)supporting
confidence: 64%
“…Animate agents followed by active verbs, passive constructions and inanimate subjects followed by active verbs or abstract rhetors have proved to be the most recurrent lexico-grammatical features associated with the writers' voice in Med-RAs. Whereas writers of academic texts claim the authorship of their work using selfmentions (Hyland 2005(Hyland , 2018aLorés-Sanz 2006Mur-Dueñas 2007;Mur-Dueñas and Šinkūnienė 2016) as the most powerful voicing mechanism, they also use passive constructions and abstract rhetors in an attempt to emphasise the research process rather that the writers' agency (Luzón-Marco 2000;Martínez 2001Martínez , 2005Vande Kopple 2002). These devoicing mechanisms allow writers to be less visible as we move down the axe of this study's cline of visibility (see Figure 2 in section 1.2), yet never absent from their texts.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the employment have identified various functions of self-mention devices across different academic genres (Afsari & Kuhi, 2016;Millán, 2010;Mur-Dueñas & Šinkūnienė, 2016) Hyland (2001), for instance, investigated the forms and functions of selfmentions used in English research articles published in eight different disciplines. The results revealed significant differences across disciplines in the employment of these features.…”
Section: Literature Reviewmentioning
confidence: 99%